UJI POTENSI ANTIBAKTERI KOMBINASI EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) DAN DAUN SESEWANUA (Cleodendron squamatum vahl.) TERHADAP BAKTERI Staphylococcus aureus - Rintjap, Djois Sugiaty; Rindengan , Elvie Rifke; Pobela, Nadila Aurelia Putri; Ulaen, Selfie Petronella Joice; Barung , Elisabeth Natalia (Jurnal Buana Farma, 2025)
Cherry leaves (Muntingia calabura L.) and sesewanua leaves (Clerodendron squamatum Vahl) can be used as an alternative antibacterial treatment. Antibacterial testing of single compositions has been widely carried out but not yet on a combination of these two plants. The study aims to determine the antibacterial potential of a combination of ethanol extracts of cherry leaves and sesewanua leaves against Staphylococcus aureus. Cherry leaves and sesewanua leaves were extracted using the maceration method, 96% ethanol solvent. The test solution was made at concentrations of 5%, 10%, and 15%. The combination was made by mixing each concentration with a ratio of 1:1. Testing using the disc diffusion method, positive control Ciprofloxacin, negative control Sodium CMC 1%, observed 1x24 hours. The inhibition zone was measured using a caliper. The average results of the inhibition zone diameter of the ethanol extract of cherry leaves were 8.74±0.25 mm, 9.27±0.15 mm, 10.21±0.30 mm, the ethanol extract of sesewanua leaves was 6.96±0.83 mm, 7.46±0.56 mm, 7.17±0.13 mm. The combination of ethanol extract of cherry leaves and sesewanua leaves was 7.51±0.49 mm, 8.30±0.61 mm, 9.70±0.20 mm, Ciprofloxacin was 26.52±3.44 mm. The best results were at a concentration of 15% but not optimal. In conclusion, single extract of cherry leaves, single extract of sesewanua leaves, combination of ethanol extract of cherry leaves and sesewanua leaves (1:1) at concentrations of 5%, 10%, and 15% have moderate antibacterial activity against Staphylococcus aureus. The inhibitory power is greater in the single extract of cherry leaves compared to the combination of extracts.